Attitude to Mathematics, Study Habit and Academic Performance of Selected Secondary Schools in Makurdi Metropolis - Musa, D.C.; Garba, Adamu (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2019)
This study examined the attitude to Mathematics, study Habit and Academic Performance of selected Secondary Schools in Makurdi. The study was anchored on theory of confluent education. The researcher used survey research design was adopted for study while the census sampling technique was utilized to determine the respondents for data analysis. A sample of 202 respondents obtained by the use of a structured questionnaire from two secondary schools in Makurdi Metropolis. The data collected were analyzed using multiple linear regression analysis. The probability value of the estimate was used in testing the hypotheses of the study. The result of the regression analysis indicates that study attitude has a positive effect on Student Attitude (STA) and Student Performance (PEF) and the relationship is statistically significant (p<0.05) and in line with a priori expectation. This means that a unit increases in on Student Attitude (STA) will result to a corresponding increase in the Student Performance (PEF) by margin of 20.8 %. Study habit (STH) was negatively related to Student Performance in selected Secondary Schools in Makurdi Metropolis (PEF) and the relationship is not statistically significant (p>0.05). It was concluded that that student attitude has a significant effect on students’ performance and academic achievement in the selected secondary schools in Makurdi Metropolis. It was recommended among others that school administrators, teachers’ and parents, should work collaboratively hand-in-hand to maximize students’ performance by helping to improve their study habit and attitude towards school. They should see to it that every needed material, resources, varied activities, and differentiated instruction are available and applied in order to cater for students' need to learn and be motivated enough.